Exploring the Human Element: A Qualitative Study of the Use of Human Resources Accounting in an Organizational Context - Tanjung, Amries Rusli; Komardi, Dadi; Renaldo, Nicholas; Reilly, William; Yu, Hou (Interconnection: An Economic Perspective Horizon, 2023)
This qualitative research explores the impact of Human Resources Accounting (HRA) on organizational dynamics, recognizing human capital as crucial for sustained success. Titled "Exploring the Human Element," the study delves into HRA, acting as a bridge between qualitative human aspects and quantitative financial demands. Despite the increasing acknowledgment of human resources' pivotal role, the intricacies of HRA implementation remain unexplored. Through in-depth interviews and thematic analysis, the research uncovers motivations, challenges, and perceived benefits of HRA in selected organizations. It introduces novel aspects, emphasizing the human element, identifying motivations and challenges, exploring perceived benefits, considering contextual nuances, integrating ethical considerations, and outlining implications for future research. The findings highlight the influence of organizational context on HRA outcomes, emphasizing the need for ethical practices. The study offers insights into motivations, challenges, and benefits of HRA adoption, paving the way for future research on longitudinal impacts, comparative analyses, and emerging technology integration. In conclusion, this research provides valuable insights for academia and practitioners, guiding organizations in strategically integrating HRA for holistic human capital management and sustainable success.